Research on Vietnamese Cultural Tourism - Huong, Hoang Thi; Thao, Xuan Thi Thu (Journal of Ecohumanism, 2025)
Vietnam is a country with great potential and advantages in building and developing cultural tourism with more than 40000 relics, including more than 10000 provincial relics, more than 3600 national relics, 128 special national relics, 15 intangible cultural heritages recognized by UNESCO. On the basis of exploiting and promoting the values ​​of cultural heritage, many localities in Vietnam have been forming and developing quite diverse cultural tourism products, such as the tourism route connecting the world heritage of ASEAN countries, the Central heritage tourism route, Hue festival, Nha Trang sea festival, Ha Long sea carnival festival, Da Lat flower festival... This study focuses on analyzing the practical development of cultural tourism in Vietnam based on a survey of localities with unique features, cultural diversity and a great role and influence on the development of the country, that is the capital Hanoi. Besides studying the core content of cultural tourism development, the author surveys and evaluates the factors affecting the cultural tourism development of Hanoi Capital, thereby discussing policy issues for reference and application to many localities in Vietnam.